On-Surface Annulation Reaction Cascade for the Selective Synthesis of Diindenopyrene - Eisenhut, Frank; Lehmann, Thomas; Viertel, Andreas; Skidin, Dmitry; Kruger, Justus; Nikipar, Seddigheh; Ryndyk, Dmitry A.; Joachim, Christian; Hecht, Stefan; Moresco, Francesca; Cuniberti, Gianaurelio (Giovanni) (ACS nano, 2017)
We investigated the thermally induced on-surface cyclization of 4,10-bis(2′-bromo-4′-methylphenyl)-1,3-dimethylpyrene to form the previously unknown, nonalternant polyaromatic hydrocarbon diindeno[1,2,3-cd:1′,2′,3′-mn]pyrene on Au(111) using scanning tunneling microscopy and spectroscopy. The observed unimolecular reaction involves thermally induced debromination followed by selective ring closure to fuse the neighboring benzene moieties via a five-membered ring. The structure of the product has been verified experimentally as well as theoretically. Our results demonstrate that on-surface reactions give rise to unusual chemical reactivities and selectivities and provide access to nonalternant polyaromatic molecules.
CRIS-Team Scopus Importer:2022-04-14
Keywords: density functional theory; nonalternant polyaromatic hydrocarbons; on-surface reaction; reaction mechanism; scanning tunneling microscopy; single-molecule chemistry